Familial Polycythemia Caused by a Novel Mutation in the Beta Globin Gene: Essential Role of P50 in Evaluation of Familial Polycythemia - Agarwal, Neeraj (Ivyspring International Publisher, 2007)
Two polycythemic subjects from a family with multiple polycythemic subjects were evaluated. Estimation of oxygen affinity of Hb from venous blood gas parameters (P50) revealed low P50 suggesting a high affinity Hb variant. Further work up, which included beta globin gene sequencing, revealed a novel mutation changing a codon to the previously reported high affinity Hb - Hb Johnstown (beta109 Val->Leu). Polycythemic subjects with high affinity Hb variant are asymptomatic with normal life expectancy. Their differentiation from polycythemia vera (PV) is crucial to avoid therapy which is otherwise reserved for PV patients. We provide an electronic version (in Microsoft excel program) of a previously reported mathematical formula for rapid calculation of P50 from venous blood gases. Estimation of P50 is an essential initial step in the evaluation of a subject with personal and family history of polycythemia.